(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
The Discomfort Thermometer (DT) is a well-established screening tool that is both sensitive and specific to the concept of cancer distress. Its shortness makes it suitable for integrating into a distress management system. A literature study was conducted to determine how far this concept has progressed in practice and to assist future research. The following databases were systematically searched: Pubmed, CINAHL, PsycINFO, Ebsco, ASSIA, British Nurses Directory, AMED, CCTR, and HMIC are just a few of the databases available. In forty studies, the DT’s function was explored alone, in conjunction using the issue list (PL), and/or other approved indicators. In order to demonstrate ‘cosiness’ in these groups and identify variables associated with distress, the bulk of research validated the DT against other strong measures of distress. Almost all of the studies suggested that their results be tested in clinical practice in the future. A tiny part of the literature looked at the DT’s clinical usefulness as a consultation facilitator and found it to be promising in this respect. It is determined that there is sufficient validation evidence, and future study should concentrate on the usefulness of DT as part of a systematic distress treatment centre, as recommended by the majority among these investigations.